ANALYSIS OF THE IMPACT OF TRANSPORTATION ACCESS ON PRICE DISPARITY AND ECONOMIC GROWTH IN THE RI-RDTL BORDER REGION - Sengkoen, Yuliati; Pangastuti, Margareta Diana (Jurnal Manajemen Bisnis Dan Organisasi, 2025)
This study aims to analyze the effect of transportation access on price disparity and economic growth in the border region between the Republic of Indonesia and the Democratic Republic of Timor-Leste (RI–RDTL). Border areas are known for their complex geographical and economic characteristics, making road access a strategic factor in promoting distribution and economic growth. This research employs a quantitative approach using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method. A total of 100 respondents were purposively selected from economic actors, local communities, and relevant institutions in the border area. The results show that road access has a negative and insignificant effect on economic growth (β = -0.182; p = 0.127) as well as on price disparity (β = -0.077; p = 0.625). Conversely, price disparity has a positive and significant effect on economic growth (β = 0.257; p = 0.027). Meanwhile, the indirect effect of road access on economic growth through price disparity is also not significant (β = -0.020; p = 0.649). These findings indicate that road access alone has not provided a significant impact on economic growth unless supported by complementary infrastructure and sound governance. Therefore, border area development needs to be carried out in an integrated manner through a holistic approach that includes strengthening infrastructure, distribution policies, and community capacity building.